The Characteristics of Coconut Phospholipids as Biosurfactants - Hudiyanti, D.; Supardi, A.; Nugroho, S. (JURNAL SAINS DAN MATEMATIKA, 2012)
All living cells consist of phospholipids. Phospholipids are known as biosurfactants. Here we report our study of the physico-chemical characteristics of phospholipids derived from coconut endosperm as biosurfactants. We studied the aggregation and emulsification characters. The aggregation proccess was examined by optical microscope. The stability of emulsi formed was montitored at different temperature and pH. Where as emulsification capability was investigated by constructing a ternary diagram. Depending on the amount of phospholipids and additive substances the emulsification capability changes. The coconut phospholipids will form vesicles in various size (polydisperse). We noticed that coconut phospholipids emulsification stability was affected by temperature, pH, and phospholipids composition. It can be concluded that the prospect of phospholipids from coconut endosperm as biosurfactants is promising. Â Keywords: coconut phospholipid, emulsification capability, aggregation, ternary diagram, vesicle.